IDENTIFIKASI FRAGMEN GEN 16S rRNA BAKTERI ASAM LAKTAT UBC-DA-08 DARI DADIH - Ike Ramadhanty Daniel; MInda Azhar (Departemen Kimia FMIPA UNP, 2019)
Bacterial identification can be done by phenotypically and genotypes use the 16S rRNA gene. This study aims to determine the species of lactic acid bacteria isolates in Dadih. The first step of identification of bacteria by screening and isolating lactic acid bacteria found in Dadih, then isolate the bacterial isolate chromosome DNA from screening (UBC-DA-08).Bacterial chromosome DNA was used as a template for amplification of the 16S rRNA gene using the PCR method.Amplikon was electrophoresed using agarose gel and purified for sequencing.Sequencing of the 16S rRNA gene was carried out using the Dideoxy-Sanger method.Sequencing bases of nucleotide sequences were analyzed using the DNAStarprogram.The 16S rRNAgene size ofthe UBC-DA-08 bacterial isolate consisted of 896 bp (base pair).The nucleotide sequence of the 16S rRNA gene can be read using the BLASTn andMEGA programs.The results of identification of UBC-DA-08 bacterial isolates were lactic acid bacteria including the Lactococcuslactis groupKeyword :Dadih, Lactic Acid Bacteria, Gene 16S rRNABacterial identification can be done by phenotypically and genotypes use the 16S rRNA gene. This study aims to determine the species of lactic acid bacteria isolates in Dadih. The first step of identification of bacteria by screening and isolating lactic acid bacteria found in Dadih, then isolate the bacterial isolate chromosome DNA from screening (UBC-DA-08).Bacterial chromosome DNA was used as a template for amplification of the 16S rRNA gene using the PCR method.Amplikon was electrophoresed using agarose gel and purified for sequencing.Sequencing of the 16S rRNA gene was carried out using the Dideoxy-Sanger method.Sequencing bases of nucleotide sequences were analyzed using the DNAStarprogram.The 16S rRNAgene size ofthe UBC-DA-08 bacterial isolate consisted of 896 bp (base pair).The nucleotide sequence of the 16S rRNA gene can be read using the BLASTn andMEGA programs.The results of identification of UBC-DA-08 bacterial isolates were lactic acid bacteria including the Lactococcuslactis group. Keyword :Dadih, Lactic Acid Bacteria, Gene 16S rRNA